Ruthenium(II)- and copper(I)-catalyzed synthesis of click-xylosides and assessment of their glycosaminoglycan priming activity. Issue 22 (15th November 2017) - Mencio, Caitlin P.; Garud, Dinesh R.; Doi, Yosuke; Bi, Yiling; Vankayalapati, Hariprasad; Koketsu, Mamoru; Kuberan, Balagurunathan
Graphical abstract: Abstract: Xylosides are small molecules that serve as primers of glycosaminoglycan biosynthesis. Xyloside mediated modulation of biological functions depends on the extent of priming activity and fine structures of primed GAG chains. In earlier studies, copper (Cu) catalyzed synthesis of click-xylosides and their priming activity were extensively documented. In the current study, ruthenium (Ru) mediated catalysis was employed to synthesize xylosides with a 1, 5-linkage between the xylose and the triazole ring instead of a 1, 4-linkage as found in Cu-catalyzed click-xyloside synthesis. Mono- and bis-click-xylosides were synthesized using each catalytic method and their glycosaminoglycan priming activity was assessed in vitro using a cellular system. Ru-catalyzed click-xylosides showed a higher priming activity as measured by incorporation of radioactive sulfate into primed glycosaminoglycan chains. This study demonstrates that altering the linkage of the aglycone to the triazole ring changes the priming activity. Computational modeling provides a molecular rationale for higher priming ability of Ru-mediated click-xylosides. Higher GAG priming activity is attributed to the formation of more stable interactions between the 1, 5-linked xylosides and β-1, 4-galactosyltransferase 7 (β4GalT7).